Mapas conceituais e resolução de problemas sobre as interações intermoleculares: um estudo com alunos da 1ª série do ensino médio - Mota, Ronaldo Nascimento (Universidade Federal de São Carlos, 2013)
The present work investigated high school students about the elaboration of conceptual maps and the resolution of their problems related to the topic intermolecular interactions. For that we based upon Ausubel's theory of meaningful learning, Concept Maps and troubleshooting. To carry out this research we use the elaboration of Concept Maps using a list of concepts extracted from their problems and that are relevant to their resolution, and the construction of the "Reference Map" according to the proposal of Joseph Novak. To make the maps the students organized hierarchically the listed contents and in accordance with the principle of progressive differentiation we determined the major conceptual deficiencies. The resolution of the problems constituted another tool for the cognitive mapping, as the students show how the concepts are organized in their minds through the application in solving the problem. The results obtained with the conceptual maps were used to trace the cognitive structuring and compared to analyzes of the resolutions of problems determining qualitative and quantitative aspects in relation to structuring and conceptual similarities in results between the two instruments. It was determined the Pearson s correlation between the results of the maps and the resolution of problems, resulting in a weak correlation between the two instruments. The reason for this is not conclusive in the extent of this research and relevant discussion originates later works. Qualitative analyzes show that the two instruments are able to determine cognitive structuring concepts and indicate their shortcomings.
Keywords: Química - estudo e ensino; Mapas conceituais; Resolução de problemas; Aprendizagem significativa; Concept maps; Troubleshooting; Meaningful learning; CIENCIAS EXATAS E DA TERRA::QUIMICA